A systematic survey of the fatty acid composition of Neurospora strains - M Goodrich-Tanrikulu; A E Stafford; D J Jacobson (Fungal Genetics Reports, 1999)
Numerous studies have examined aspects of lipid metabolism in Neurospora crassa, N. tetrasperma and N. sitophila, but little systematic comparison has been done on lipids of the different species. Most obviously missing, however, is comparison of the fatty acid composition of lipids among Neurospora species. Fatty acid composition (especially the production of particular polyunsaturated fatty acids) is often a key factor in genus or species identification, particularly in bacteria, but also in other fungi such as Aspergillus, Penicillium and Mortierella (Kock and Botha 1998 In Frisvad et al. (eds), Chemical Fungal Taxonomy, Marcel Dekker, NY, p. 219-246). Until this study, reports of the fatty acid composition of Neurospora lipids have been limited to a few laboratory strains of N. crassa.